INDEKS PENILAIAN KEAMANAN INFORMASI UNTUK MENGUKUR KEMATANGAN MANAJEMAN KEAMANAN LAYANAN TI (Studi Kasus BPMP Kabupaten Gresik) - Rahmat Hidayat; Mohammad Suyanto; Andi Sunyoto (Informasi Interaktif, 2018)
This study contains the results of measurement of the maturity of Information Security Management System (ISMS) in the Gresik District The result of measurement of the completeness and maturity of the ISMS in BPMP Gresik Regency is still relatively low, that is at the level of I to II which means the maturity level is stated in the initial condition up to the implementation of the basic framework, it is still under standard ISO 27001: 2009. And for the evaluation of the level of completeness of the implementation of the five areas with the achievement score of 207, then according to the Indeks KAMI mean readiness status is considered "Not Eligible". The causes of the low maturity level of the ISMS include low levels of awareness from the leadership and related employees of the ISMS, lack of documentation of activities and also for the development of applications and infrastructure that are reactive.Researchers suggest of things need to increase awareness to leaders and employees regarding the importance of the ISMS, and to develop ICT Blueprint that enables BPMP application development and infrastructure to be conducted in a planned and comprehensive manner. And improve SOP in BPMP environment to support business process shift from paper-based to technology-based administration as well as to cultivate the documentation of data and information in BPMP Gresik District. Keywords: ISMS, BPMP Gresik District, index KAMI, ISO2700:2009